Dental implants in the elderly population: a systematic review and meta‐analysis. Issue 8 (7th June 2016) - Srinivasan, Murali; Meyer, Simon; Mombelli, Andrea; Müller, Frauke
Abstract: Objective: This systematic review was conducted to evaluate the outcome of dental implant therapy in elderly patients (≥65 years). Material and Methods: Online database and hand searches were systematically performed to identify studies reporting on dental implants placed in the partially/completely edentulous jaws of elderly patients. Only prospective studies reporting on regular‐diameter (≥3 mm), micro‐rough surface implants were included in this review. Two investigators performed the search and data extraction. An inter‐investigator reliability was verified using kappa statistics (κ). A meta‐analysis was performed on implant survival rates, while the mean peri‐implant marginal bone level changes (PI‐MBL), technical/mechanical complications, and biological complications were reported descriptively. Results: The systematic search yielded 2221 publications, of which 11 studies were included for statistical analyses. The calculated κ for the various parameters extracted was κ = 0.818–1.000. A meta‐analysis was performed on the post‐loading implant survival rates at 1, 3, 5, and 10 years. The random‐effects model revealed an overall 1‐year implant survival of 97.7% (95% CI: 95.8, 98.8; I 2  = 0.00%, P  =   0.968; n  = 11 studies). The model further revealed an overall implant survival of 96.3% (95% CI: 92.8, 98.1; I 2  = 0.00%, P  =   0.618; n  = 6 studies), 96.2% (95% CI: 93.0, 97.9; I 2  = 0.00%, P  =   0.850; n  = 7 studies), and 91.2% (95% CI: 83.4, 95.6; I 2  = 0.00%, P  =   0.381; n  = 3 studies) for 3, 5, and 10 years, respectively. The reported 1‐year average PI‐MBL ranged between 0.1 and 0.3 mm, while the reported 5‐ and 10‐year PI‐MBL were 0.7 and 1.5 mm, respectively. Information obtained pertaining to the technical and biological complications in the included studies was inadequate for statistical analysis. The frequent technical/mechanical complications reported were abutment screw loosening, fracture of the overdenture prostheses, activation of retentive clips, ceramic chipping, and fractures. The common biological complication reported included peri‐implant mucositis, mucosal enlargement, bone loss, pain, and implant loss. Conclusions: This review provides robust evidence favoring dental implant therapy in elderly patients as a predictable long‐term treatment option, in terms of implant survival, clinically acceptable PI‐MBL changes, and minimal complications. Therefore, age alone should not be a limiting factor for dental implant therapy.